1985
DOI: 10.1038/sc.1985.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different methods of bladder drainage used in the early care of spinal cord injury patients

Abstract: SUIDIDaryIn a series of 115 spinal cord injury patients four different methods of bladder drainage were used mainly during spinal shock. That is a) suprapubic fine bore cystostomy, b), indwelling Foley catheter, c) intermittent catheterisation; and d) both last methods consecutively.The methods of bladder drainage used did not influence the number of patients becoming catheterfree but determined significantly the length of period before patients became catheterfree. Patients on intermittent catheterisation had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…4 ± 7 CIC may not be as e ective if the bladder is hyperre¯exive with detrusor-sphincter dyssynergia. 4,6 When CIC plus anticholinergic program failed to create an adequate bladder volume with lower pressure during storage, bladder augmentation is generally considered. 8 The purpose of this study is to assess the possibility of augmentation cystoplasty to achieve safe long-term urologic management in SCI patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 ± 7 CIC may not be as e ective if the bladder is hyperre¯exive with detrusor-sphincter dyssynergia. 4,6 When CIC plus anticholinergic program failed to create an adequate bladder volume with lower pressure during storage, bladder augmentation is generally considered. 8 The purpose of this study is to assess the possibility of augmentation cystoplasty to achieve safe long-term urologic management in SCI patients.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Informed consent must be obtained from SCI patients for TOM. (2) Check whether the patient will be able to wear a penile sheath and the sheath will stay in place when the patient is sat up on the chair.…”
Section: Discussionmentioning
confidence: 99%
“…Where IDC for longer than 6-8 weeks is antici pated, an alternative, such as suprapubic fine-bore catheterisation, may be a better alternative and should be considered more often; studies with its use in recent years have shown encouraging results. 18,19 As the purpose of this paper is to establish some guidelines for the frequency of radiological surveillance during the lifetime of the SCI patients, no attempt has been made to establish a relationship with variables such as inefficient bladder emptying, high detru sor pressure, disturbance of bladder com pliance, and/or high resistance to urinary flow. It should be appreciated that uro logical complications in patients who are catheter free are influenced by these factors.…”
Section: Discussionmentioning
confidence: 99%